(untitled) (International Journal of Automation and Smart Technology, 2011)
The measurement of the relative post-weld-shift (PWS) in the butterfly-type laser module packaging processes is very difficult because the components are very small and the space is very compact. In this paper, we develop a low cost system to study the feasibility on the on-line measurements of PWS in a butterfly-type laser module packaging process. The main components of the system are three 5 mW commercial lasers, three 2-axis position sensing detectors (PSD), and three micro mirrors. The system developed in this paper can measure the three Degrees of Freedom (DOF) of displacement of the optical fiber ferrule after PWS. The displacement measurement system is implemented on a Newport butterfly-type laser diode module package station (Model LW4200) for testing. The resolution of this system is within 1 μm and the accuracy is within 2 μm.